2020
DOI: 10.1002/rcs.2117
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury and its impact on renal prognosis after robot‐assisted laparoscopic radical prostatectomy

Abstract: Background: This study assessed the incidence and impact of acute kidney injury (AKI) on renal prognosis in patients who underwent robot-assisted laparoscopic radical prostatectomy (RARP). Methods: Medical records of 305 patients treated with RARP were retrospectively reviewed. The patients with postoperative AKIs were dichotomized into early AKI (immediately after surgery) and late AKI (1-7 days after surgery). The impact of AKIs and their risk factors were statistically assessed. Results: Early and late AKI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…There are some studies stating that there is no association between intraoperative urine output and the occurrence of AKI 30 , 31 , while others are advocating for the association between oliguria and the occurrence of AKI after major non-cardiac surgery 28 , 32 , 33 . Although some previous studies investigated the risk factors for AKI after RALP, none of those included the urine output as a candidate variable 6 8 . Therefore, our study is the first to identify the low intraoperative urine output as a risk factor for AKI in RALP.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are some studies stating that there is no association between intraoperative urine output and the occurrence of AKI 30 , 31 , while others are advocating for the association between oliguria and the occurrence of AKI after major non-cardiac surgery 28 , 32 , 33 . Although some previous studies investigated the risk factors for AKI after RALP, none of those included the urine output as a candidate variable 6 8 . Therefore, our study is the first to identify the low intraoperative urine output as a risk factor for AKI in RALP.…”
Section: Discussionmentioning
confidence: 99%
“…The AKI incidence in our study was 2.4%, which is half of the previously reported incidence (5%) in RALP 5 , 6 . Some studies have demonstrated that a longer operation time represents a risk factor for AKI after RALP 6 8 . Therefore, our low AKI incidence could be attributed to shorter operation times than those observed in previous studies in which the mean operation time was around 170–180 min 6 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations